Multiplex-PCR for diagnosis of bacterial meningitis - Albuquerque, Renata Chaves (Braz J Microbiol, 2019)
Considering the great lethality and sequels caused by meningitis, rapid diagnosis and prompt treatment initiation have a great impact on patient outcome. Here, we developed a multiplex-PCR for simultaneous detection of the four most prevalent bacterial pathogens directly in CSF samples. The multiplex-PCR was designed to detect the following genes: fbsA (Streptococcus agalactiae), lytA (Streptococcus pneumoniae), crtA (Neisseria meningitidis), p6 (Haemophilus influenzae), and 16S rRNA (any bacterial agent). The multiplex-PCR showed a DNA detection limit of 1 pg/μL. Among 447 CSF samples tested, 40 were multiplex-PCR positive, in which 27 and 13 had positive and negative bacterial culture, respectively. Our multiplex-PCR is fast, reliable, and easily implementable into a laboratory routine for bacterial meningitis confirmation, especially for patients who previously started antimicrobial therapy. Our molecular approach can substantially improve clinical diagnosis and epidemiological measures of meningitis disease burden.